The Influence of Shopee Instant Delivery Service, Cash on Delivery (COD), and Product Price on Purchase Decisions for Fashion Products in Medan City - Juliani phannoto; Kristi Endah Ndilosa Ginting; Mella Yunita (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The rapid expansion of e-commerce in Indonesia has significantly reshaped consumer purchasing behavior, particularly in the fashion sector. This study examines how Shopee’s Instant Delivery Service, Cash on Delivery (COD), and product pricing influence purchase decisions among fashion consumers in Medan City. A quantitative research design was employed, using a survey, with data collected from 300 Shopee users selected through purposive sampling. The results indicate that Shopee Instant Delivery Service, COD, and product price each exert a positive and significant effect on purchase decisions. Among these factors, product price exerts the strongest influence, underscoring consumers’ high sensitivity to price in online fashion transactions. Simultaneously, all three variables significantly explain variations in purchase decisions, with a coefficient of determination (R²) of 0.490. These findings underscore the strategic importance of integrating fast delivery services, secure and flexible payment options, and competitive pricing strategies to strengthen consumer purchase decisions on e-commerce platforms. This study contributes to the e-commerce literature by providing empirical evidence from a metropolitan area outside Java, where consumer behavior remains relatively underexplored